The Acceptance of Biogas in Islamic Boarding School Surakarta - Amining Rahmasiwi (Sustinere: Journal of Environment and Sustainability)
The increasing population growth in Indonesia has an impact on increasing energy needs and depleting global energy sources. One of the ways to fulfill high global energy levels can be through the use of renewable energy in the form of biogas. This research is qualitative research that aims to determine the response of the pesantren community in Central Java regarding the application of biogas. The analysis was carried out interactively by describing the data in a qualitative narrative manner from the questionnaires that had been filled out by the respondents. The results showed that the response to the acceptance of the use of biogas in the Central Java Islamic Boarding School Community as an effort to accelerate the national renewable energy mix was also still diverse. However, in one respect their response is the same, namely while bringing benefits, they agree, but on the condition that it is safe, not from unclean materials, and the place or location for biogas development must be adequate. Based on the exploration of the ten, it seems that the government’s program in fulfilling renewable energy still needs to be optimized for socialization and its approach in Islamic boarding schools.